Harmonization of Piece-by-Piece Measurement Methods of Roundwood Approved by Latvian Standard LVS 82:2003 “ Apaļo kokmateriālu uzmērīšana ” (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper analyses the volume differences of mixed pine and spruce roundwood loads and logs (roundwood assortiments) devided in to sample clusters according to the species, diameter, lenght and stem/log surface shape, stem zones and measured by the methods approved by standard LV 82:2003 „Apaļo kokmateriālu uzmērīšana”. The volumes of roundwood loads/logs determined by these methods were compared with the most precisious determination of the volume by Measuring Diameter in Short Intervals and the Top and Butt Diameter Measurement method. The volume of mixed pine and spruce round timber load determined by Measuring Diameter in Short Intervals using harvester measurement system is 2.44% higher than the volume determined by manual comparative the Top and Butt Diameter Measurement method. The volume deviation is in the range of accepted 3% measuring accuracy. The volumes of roundwood assortiments from neiloid zone of spruce stems determined according to the Mid Diameter Measurement method are 3.96% lower than the volumes determined by careful manual the Top and Butt Diameter Measurement method. The volume deviation surpass the acceptable measuring 3% accuracy. The volumes of roundwood assortiments from paraboloid zone of spruce and pine stems determined according to the Mid Diameter Measurement method are lower than the volumes determined by the Top and Butt Diameter Measurement method. The deviation is in the range of acceptable 3% measuring accuracy. This paper gives recommendations for adjusting the application area of different measurement methods for achieving the volume deviation in the range of accepted measuring accuracy.